Testicular ultrasound evaluation in small animal practice - Magalhães, Francisco Felipe de; Souza, Mírley Barbosa de; Silva, Lúcia Daniel Machado da (Medicina Veterinária, 2019)
Ultrasonographic imaging allows a detailed evaluation of the testicles of dogs and cats. It has been used as a tool for reproductive evaluation as well as for the detection of conditions that can affect the gonads. B-mode ultrasound evaluates the echogenicity, echotexture, and testicular volume parameters and, using the Doppler tool, the vascularization is evaluated at that location. Contrast-enhanced ultrasound provides information about the microvasculature, which may suggest a possible vascular impairment affecting fertility. Although most testicular pathologies can be detected by these techniques, there are still concerns about the differential diagnosis and better understanding of the ultrasound imaging resulting from these conditions. Due to the great importance of this tool, this study aims to conduct a review on the use of testicular ultrasound of dogs and cats, exploring the normal and abnormal characteristics observed in each exam and the perspective on the use of contrast agents in the evaluation of gonads of these animals.